Delta-V-Based Cooperative Strategies for Orbital Two-Pursuer One-Evader Pursuit–Evasion Games - Sihan Xu; Liran Zhao; Weichen Zhang; Zhaohui Dang (Space: Science & Technology)
This paper investigates the application of the Nash equilibrium solution method within 2-versus-1 impulsive orbital pursuit–evasion (P-E) scenarios, involving 2 pursuers and an evader. Through the integration of game theory and coordinated strategies between the pursuers, the initial 2-pursuer 1-evader game (([Formula: see text]) - E) is transformed into a composite 1-pursuer 1-evader game (P2 - (P1 - E)). To address the core challenge of the P-E game, we utilize the MinMax bilateral optimization algorithm to determine optimal strategies in each game iteration, ensuring fairness and equal opportunities for all involved parties. Within the composite P-E framework, the second pursuer ([Formula: see text]) assumes responsibility for executing a coordinated pursuit strategy, including the evaluation and tracking of the anticipated outcome of [Formula: see text]. Subsequently, the evader formulates an optimal counterplay by reverse engineering the potential role assignments and strategies of the pursuers. In order to explore the intricate aspects of these scenarios, our study harnesses Monte Carlo statistical methods, offering insights into critical factors such as initial positions, impulse intervals, and magnitudes of delta-V within orbital settings, all of which substantially influence game outcomes. Ultimately, this research not only advances our understanding of multiagent orbital P-E dynamics but also establishes a foundation for more informed and effective strategic planning in practical space missions. It aims to ensure mission success and responsible resource allocation in the domain of space exploration.